Case report: Metastatic Merkel cell carcinoma presenting seven years after loco-regional disease resection of primary tumor with interval in-transit and nodal metastases - Rusheen, Joshua; Clune, James; Ariyan, Stephan; Baumann, Raymond; Kluger, Harriet; Olino, Kelly; Weiss, Sarah (Frontiers in Oncology, 2023)
Merkel cell carcinoma (MCC) is a rare tumor with a high risk of recurrence after definitive therapy, however the optimal duration of surveillance is unclear. First recurrences typically occur within three years. National guidelines recommend that patients undergo physical examination and imaging for surveillance during this time period. However, the duration of surveillance beyond this is not defined. Here we describe a case of a patient developing a recurrence of MCC 7 years after the primary diagnosis with interval in-transit and regional lymph node metastases 15 months following the treatment of the primary MCC. Such late recurrences are rare, largely not reported, and the risk factors contributing to late recurrences are not well described. This case highlights the possibility of late recurrences of MCC after an initial in-transit and nodal recurrence and underscores the importance of identifying predictors of recurrence that may better guide the duration of surveillance.